Parapharyngeal branchial cleft cyst: a case report - Oliveira dos Santos, Marcele; Girardi, Adriana; Muradás Girardi, Fábio; Hauth, Luiz Alberto; Weber, Viliam Gustavo (Clinical and Biomedical Research, 2015)
A 30-year-old woman presented with a 2-year history of right-sided pharyngeal foreign body sensation. There were no signs of dysarthria, dysphagia, odynophagia, or dyspnea. On physical examination, we observed a fluctuant, painless mass in the oropharynx, pressing against the right lateral pharyngeal wall, covered with normal mucosa. Full examination of the head and neck, including cranial nerve evaluation, detected no further abnormalities.